PEMBIAYAAN KENDERAAN BERKONSEPKAN AL-IJARAH THUMMA AL-BAY' (AITAB) DI BANK MUAMALAT MALAYSIA BERHAD DAN ISU-ISU BERKAITAN: Vehicle Financing Based on the al-Ijarah Thumma al- Bay' (AITAB) Concept at Bank Muamalat Malaysia Berhad and Related Issues - Zakaria, Mohd Usoff; Ab Ghani, Ab Mumin (Jurnal Syariah, 2017)
AITAB is an Islamic concept which has been used widely by many financial institutions in Malaysia, especially for the vehicle financing product. This consumer product, which is in high demand in the market, is also offered by Bank Muamalat Malaysia Berhad (BMMB). AITAB has been designed under the purview of the conventional Hire-Purchase Act 1967, but, at the same time, it has to comply with Shariah requirements. It involves two essential contracts which must be implemented separately and continuously, thus, the process involved seems to be more complicated than a single act of signing and documentation. This study aims to describe the implementation of this concept at BMMB and to identify ways to overcome the difficulties in managing it, as highlighted above. Furthermore, the common perception amongst customers, based on past findings, indicates that it is similar to the conventional product. Therefore, this study also tries to increase the understanding and knowledge of the product amongst the public, particularly in terms of its operation and other related issues. There are some issues and challenges which need to be reviewed by BMMB in other to develop this facility further and to make it more competitive in the market. Stiff competition in the industry, lack of knowledge among the public, poor operational structure and poor collection and recovery approaches are among the issues and challenges highlighted. Last but not least, even though the total assets of Islamic hire purchase financing using AITAB are increasing nationwide, the percentage is uncertain due to national policy requirements to reduce household debt by tightening its terms and procedures. The purpose of this policy is to mitigate the high risk of financing, which includes the easy decrease in value, defaults on repayment and difficulties in repossessing and to be more concerned about the quality of the asset.